Languages, Design Methods, and Tools for Electronic System Design Selected Contributions from FDL 2015 - Drechsler, Rolf.; Wille, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book brings together a selection of the best papers from the eighteenth edition of the Forum on specification and Design Languages Conference (FDL), which took place on September 14-16, 2015, in Barcelona, Spain. FDL is a well-established international forum devoted to dissemination of research results, practical experiences and new ideas in the application of specification, design and verification languages to the design, modeling and verification of integrated circuits, complex hardware/software embedded systems, and mixed-technology systems. Covers Assertion Based Design, Verification & Debug; Includes language-based modeling and design techniques for embedded systems; Covers design, modeling and verification of mixed physical domain and mixed signal systems that include significant analog parts in electrical and non-electrical domains; Includes formal and semi-formal system level design methods for complex embeddedsystems based on the Unified Modelling Language (UML) and Model Driven Engineering (MDE).
Introduction -- Virtual Hardware-In-The-Loop Co-Simulation for Multi-Domain Automotive Systems via the Functional Mock-Up Interface -- Standard Compliant Co-Simulation Models for Verification of Automotive Embedded Systems -- Building a Dynamically Reconfigurable System Through a High-Level Development Flow -- A Special-Purpose Language for Implementing Pipelined FPGA-based Accelerators -- Enabler-Based Synchronizer Model for Clock Domain Crossing Static Verification -- Temporal Decoupling with Error-Bounded Predictive Quantum Control -- Conservative Behavioural Modelling in SystemC-AMS -- Modeling Power Consumption at System-Level for Design of Power Integrity-Aware AMS-Circuits.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation